Examination and diagnosis of common craniomandibular disorders - Dickinson Anthony J. (Sciendo, 1989)
The disorders of the craniomandibular complex are often a combination of disorders of the temporomandibular joint itself as well as the orofacial and neck muscular. A definitive diagnosis and subsequent treatment plan can only be reached by gaining sufficient information to allow a decision as to which components of the craniomandibular complex, and to what extent, are contributing to the patients problem. A systematic approach to an examination procedure commencing with a simple screening evaluation is cliscussed, which, when followed, will allow a differsndal diagnosis.